Analytical Study of the Value of Religious Moderation in the Medina Charter Agreement in the History of Islamic Culture in MI - Marsha Aulia Salwa; Akhir Aulia; Isna Zahratunnisa; Dian Nely Ma'rifah; Adelia Maulidya; Dina Aulia Rahma; Dian Rif'iyati (Al-Mudarris, 2026)
Islamic education plays a strategic role in shaping the character of a tolerant and inclusive younger generation within society. Particularly in the subject of Islamic Cultural History (SKI) at the Madrasah Ibtidaiyah level, instilling noble values from an early age becomes the foundation of national diversity. The Constitution of Medina, as the first constitution in Islam, offers a model of harmonious interfaith relations based on justice and tolerance. However, the challenges of globalization and radicalism demand that historical values be revitalized in the learning process. The internalization of religious moderation through SKI is not merely a transfer of knowledge, but also an effort to build a moderate character. This study aims to analytically examine the values of religious moderation contained in the Constitution of Medina and their relevance in the implementation of SKI learning at Madrasah Ibtidaiyah. This study employs a qualitative method with a library research approach, analyzing various written references related to the research topic. The data sources include books, scientific journals, and findings from previous studies. The results show that the Constitution of Medina contains values of religious moderation such as tolerance, justice, freedom of religion, deliberation, and peace as reflected in its various articles. These values are relevant to be integrated into SKI learning at Madrasah Ibtidaiyah as an effort to shape students’ moderate character, foster respect for diversity, and enable them to live harmoniously in a pluralistic society.